More Than Just a Cough: A Dual Diagnosis of Lung Carcinoma and Hidden Hookworm Infection - Alisa Hanum, Arba’eni @ Arbaen; Nurdiyana, Zakaria; Norashikin, Samsudin; Nurnabilah, Zainuddin; Romano, Ngui
Chronic respiratory symptoms often raise suspicion for pulmonary tuberculosis (PTB), especially in high-prevalence regions. However, a broad differential diagnosis is essential, particularly when initial investigations return negative. This case illustrates the value of comprehensive assessment in uncovering multiple und apparently straightforward presentation.